Validation of a Turkish Translation of the Perceived Occupational Stress Scale and Measurement Invariance Across Turkish and Italian Workers - Yıldırım M; Dilekçi Ü; Marcatto F; Gómez-Salgado J (Dove Medical Press, 2024)
Murat Yıldırım,1,2 Ümit Dilekçi,3 Francesco Marcatto,4 Juan Gómez-Salgado5,6 1Department of Psychology, Faculty of Science and Letters, Agri Ibrahim Cecen University, Agri, Turkey; 2Department of Social and Educational Sciences, Lebanese American University, Beirut, Lebanon; 3Department of Child Development, Batman University, Batman, Turkey; 4Department of Life Sciences, University of Trieste, Trieste, Italy; 5Department of Sociology, Social Work and Public Health, Faculty of Labour Sciences, University of Huelva, Huelva, Spain; 6Safety and Health Postgraduate Program,Universidad Espíritu Santo, Guayaquil, EcuadorCorrespondence: Murat Yıldırım, Department of Psychology, Faculty of Science and Letters, Agri Ibrahim Cecen University, Fırat Mahallesi Yeni Üniversite Caddesi, No: 2 AE/1 04100 Merkez, Ağrı, Turkey, Email muratyildirim@agri.edu.tr; muratyildirimphd@gmail.com Juan Gómez-Salgado, Department of Sociology, Social Work and Public Health, Faculty of Labour Sciences, University of Huelva, Avenida Tres de marzo, s/n, Huelva, 21007, Spain, Tel +34 959219700, Email salgado@uhu.es; jgsalgad@gmail.comIntroduction: Measuring and understanding perceived occupational stress is crucial for understanding workers' experiences of stress in the workplace and its potential implications on mental health outcomes and job performance. However, there is a scarcity of brief measures containing relevant items focused solely on occupational stress, suitable for integration with risk assessment tools for work-related stress. This study aimed to validate the Perceived Occupational Stress (POS) scale in Turkish and examined its measurement invariance across Turkish and Italian samples.Methods: The participants included 350 Turkish teachers (55.7% male) and 160 Italian workers (60.6% female).Results: The results showed a single-factor structure explaining 69.61% of the total variance for the POS. The internal consistency was found to be high in both samples. The results also indicated that the factor structure of the POS was equivalent across the two groups, supporting measurement invariance.Conclusion: Overall, the POS demonstrated solid measurement properties, including validated factor structure, internal reliability, and measurement invariance.Keywords: perceived occupational stress, work-related stress, measurement invariance, cross-cultural comparisons, Turkish transcultural translation, validity and reliability